Nigeria Development Update, June 2020 : Nigeria in Times of COVID-19 - Laying Foundations for a Strong Recovery - World Bank (World Bank, Washington, DC, 2020)
This edition of the Nigeria Development Update provides policy options that Nigerian policymakers may consider in order to mitigate the impacts of COVID-19 (coronavirus) and lay the foundation for a strong recovery. These policy options are organized in the five areas: 1. Containing the COVID-19 outbreak and preparing to deal with a more severe outbreak; 2. Enhancing macroeconomic management to boost investor confidence; 3. Safeguarding and mobilizing revenues; 4. Reprioritizing public spending to protect critical development expenditures; 5. Supporting economic activity and provide relief for poor and vulnerable communities.